Hybrid Microstrip Diplexer Design for Multi-band WiMAX Application in 2.3 and 3.5 GHz Bands - M. A. Sazali; N. A. Shairi; Z. Zakaria (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this paper, a design of hybrid microstrip diplexer is proposed for multi-band Worldwide Interoperability for Microwave Access (WiMAX) application in 2.3 and 3.5 GHz bands. The diplexer consists of a combination of two different filter designs. These filters were designed based on microstripline coupling techniques in order to obtain minimum insertion losses and achieve the desired frequency bandwidth. Therefore, a coupled open loop ring resonator was chosen for the filter design in 2.3 GHz band and a folded coupled line resonator was chosen for the filter design in 3.5 GHz band. Then, these filters were combined with a ring manifold matching network to be a hybrid microstrip diplexer. Based on the results, good agreements were achieved between the simulation and measurement results in terms of insertion loss, return loss and bandwidth in the 2.3 and 3.5 GHz bands.